Experiences and perceptions of patients undergoing treatment and quality of life impact of diabetic macular edema: a systematic review. Issue 4 (21st April 2019) - Rose, Monique Anne; Vukicevic, Meri; Koklanis, Konstandina; Rees, Gwyneth; Sandhu, Sukhpal; Itsiopoulos, Catherine
ABSTRACT: Diabetic macular edema (DME) is a common cause of visual impairment. Current treatments for DME include laser photocoagulation, corticosteroids and Vascular Endothelial Growth Factor (VEGF) antagonists, which are administered via intravitreal injection. The purpose of this systematic review is to explore the experiences and perceptions of patients undergoing laser, corticosteroid implants and intravitreal injection treatment for DME and the impact on Quality of Life (QoL). A systematic search of the Embase, Medline, PsycINFO and Cinahl electronic databases was conducted to identify all studies with an unlimited date range, published in the English language, full text and incorporating human participants. Hand searching identified two articles. Following the application of the Critical Appraisal Skills Programme (CASP) Quantitative and Qualitative Research Checklist 21 articles were selected for inclusion, as they were deemed pertinent for the purpose of this review. Limited studies have examined DME patients' experiences and perceptions of treatment and QoL. The outcomes of these studies lack agreement on the effectiveness of treatment, treatment preferences and impact of QoL in patients with DME. Future research which enhances current knowledge will therefore serve to improve treatment outcomes and QoL in these patients.